Monitoring Monitoring : Assessing Results Measurement at the World Bank - Cotlear, Daniel; Kronick, Dorothy (World Bank, Washington, DC, 2014)
This paper documents a review of results monitoring in the portfolio of the Latin America and Caribbean Region Human Development Department (LCSHD) of the World Bank. While several aspects of results monitoring have improved in recent years, and while a focused department-level action plan made additional progress, further improvements require Bank-wide action. Specifically, the report finds that the Bank does not have a fully functioning system of results monitoring. The Bank does not have a set of rules or procedures governing the measurement of development results, nor does it have a physical platform for reporting results, nor an incentive structure designed to encourage results monitoring. The paper discusses this finding along with potential recommendations.